Through the Economic Cost of Discrimination: The Way forward for Women in the Somali Customary Justice System (Strathmore Law Review, 2020)
The Constitution of Kenya guarantees the promotion of customary justice systems. However, in many cases, the dictates of customary law are often in contravention with the progressive attitude embodied in the Constitution. The Constitution guarantees the right to equal treatment of men and women in social, political and cultural spheres. However, women in the Somali customary justice system do not enjoy this right. Women in the Somali customary justice system have no locus standi before any dispute resolution process and they cannot oversee the resolution of disputes as this position is reserved for the elders, who can only be men. Through Gary Becker’s theory on the economics of discrimination, this paper establishes, through an economic lens, that there is a prevailing cost to the Somali community for failing to include women in the processes of the customary justice system. It suggests a way forward of promoting inclusivity in line with the characteristics of customary law.